INVESTIGATING DECLARATIVE KNOWLEDGE OF PROFESSIONAL TRANSLATORS - Nababan, M.R (Universitas Muhammadiyah Surakarta, 2006)
Declarative knowledge is a belief system of translators which underlies the prac- tices of translating. It guides translators in decision-making process in an interlingual communication. Exploited simultaneously and effectively with operative knowl- edge it results in the production of a quality. In some cases, as evidenced in process- oriented studies, there is a gap between the two to the extent that what translators know and believe about translation does not match what they do in practices. Key words: Declarative knowledge, translation, and competence.